2020
DOI: 10.1038/s41467-020-16103-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conserved NSL complex/BRD4 axis controls transcription activation via histone acetylation

Abstract: Cells rely on a diverse repertoire of genes for maintaining homeostasis, but the transcriptional networks underlying their expression remain poorly understood. The MOF acetyltransferasecontaining Non-Specific Lethal (NSL) complex is a broad transcription regulator. It is essential in Drosophila, and haploinsufficiency of the human KANSL1 subunit results in the Koolen-de Vries syndrome. Here, we perform a genome-wide RNAi screen and identify the BET protein BRD4 as an evolutionary conserved co-factor of the NSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Other KATs and acetylation events also influence gene activity at multiple levels. For example, Gaub et al (2020) found that in both Drosophila and mouse embryonic stem cells (mESCs), acetylation of H4 by the NSL (non-specific lethal) complex is important for the maintenance of activity of constitutively expressed genes through recruitment of the Brd4 (bromodomain containing 4) reader protein. Consistent with these results, haploinsufficiency of the KANSL1 subunit (KAT8 regulatory NSL complex subunit 1) of the NSL complex is associated with Koolen-de Vries syndrome, and patient-derived fibroblasts show altered expression of constitutive genes required for cellular homeostasis.…”
Section: Levels Of Gene Transcriptionmentioning
confidence: 99%
“…Other KATs and acetylation events also influence gene activity at multiple levels. For example, Gaub et al (2020) found that in both Drosophila and mouse embryonic stem cells (mESCs), acetylation of H4 by the NSL (non-specific lethal) complex is important for the maintenance of activity of constitutively expressed genes through recruitment of the Brd4 (bromodomain containing 4) reader protein. Consistent with these results, haploinsufficiency of the KANSL1 subunit (KAT8 regulatory NSL complex subunit 1) of the NSL complex is associated with Koolen-de Vries syndrome, and patient-derived fibroblasts show altered expression of constitutive genes required for cellular homeostasis.…”
Section: Levels Of Gene Transcriptionmentioning
confidence: 99%
“…The NSL complex was found to bind to ll Article promoters of housekeeping genes in Drosophila cells and to stimulate expression of a subset of these genes (Feller et al, 2012;Lam et al, 2012;Raja et al, 2010). Particularly, NSL complex depletion was shown to reduce RNA polymerase II (Pol II) (Gaub et al, 2020;Lam et al, 2012), TBP (Lam et al, 2012), TFIIB (Lam et al, 2012), and BRD4 (Gaub et al, 2020) binding and to induce loss of nucleosome-free regions at target promoters (Lam et al, 2019). Although it is currently unknown how the NSL complex directly contributes to this regulation, many attribute these phenotypes to H4K16 acetylation, as the main catalytic activity of KAT8 (Gaub et al, 2020;Sheikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The NSL HAT complex has been reported to be a broad transcription regulator of constitutively expressed genes in both flies and mammals [ 45 , 46 ]. Our cell proliferation and colony formation experimental results ( Figure 2 C,D,G) suggested that there was a mutual regulatory relationship between NSL HAT and YY1.…”
Section: Resultsmentioning
confidence: 99%